2015
DOI: 10.2147/ott.s91460
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of secreted frizzled-related proteins is associated with aberrant β-catenin activation in the carcinogenesis of oral submucous fibrosis

Abstract: Secreted frizzled-related proteins (SFRPs), the first identified Wnt antagonists, have been well recognized as tumor suppressors in multiple human cancers through suppressing the Wnt/β-catenin pathway. To better elucidate the mechanisms of SFRPs involved in the carcinogenesis of oral submucous fibrosis (OSF), one of the precancerous lesions of oral squamous cell carcinoma (OSCC), we investigated expression and localization of SFRP1, SFRP5, and β-catenin in normal oral epithelium, OSF, and OSCC tissues. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Additionally, SFRP2 was found methylated in the majority of OSCC samples, in contrast to corresponding normal mucosa, and its overexpression reduced tumor growth in vivo [72]. It was shown that the reduction in SFRP1 and SFRP5 expression, which was induced by gene promoter methylation, was associated with cytoplasmic/nuclear delocalization of β-catenin in oral lesions [73]. Apart from SFRP1 and SFRP2, also WIF1, DKK1 and PPP2R2B were methylated in LSCC cell lines and primary tumors [74].…”
Section: The Role Of Epigenetic Mechanisms In Wnt/β-catenin Pathway Amentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, SFRP2 was found methylated in the majority of OSCC samples, in contrast to corresponding normal mucosa, and its overexpression reduced tumor growth in vivo [72]. It was shown that the reduction in SFRP1 and SFRP5 expression, which was induced by gene promoter methylation, was associated with cytoplasmic/nuclear delocalization of β-catenin in oral lesions [73]. Apart from SFRP1 and SFRP2, also WIF1, DKK1 and PPP2R2B were methylated in LSCC cell lines and primary tumors [74].…”
Section: The Role Of Epigenetic Mechanisms In Wnt/β-catenin Pathway Amentioning
confidence: 99%
“…The expression of Wnt ligand antagonist WIF1 is observed in normal oral epithelium, suggesting that WIF1 plays a role in the inhibition of canonical Wnt signaling in healthy mucosa. However, the expression of WIF1 was much lower in OSCC samples [59], and this was related to the methylation of WIF1 promoter [73]. The methylation of WIF1 in OSCC was found to be cancer-specific when compared to normal mucosa [73,75].…”
Section: The Role Of Epigenetic Mechanisms In Wnt/β-catenin Pathway Amentioning
confidence: 99%
See 2 more Smart Citations
“…WIF1 promoter methylation may account for the β-catenin activation characteristic of OSF carcinogenesis [85]. In contrast, promoter methylation suppresses the secretion of the frizzled-related proteins 1 (SFRP1) and SFRP5 and are coupled with cytoplasmic/nuclear β-catenin accumulation in OSF carcinogenesis [86]. β-catenin expression levels in the normal, hyperplastic, dysplastic, and OSCC stages of OSF merit further investigation.…”
Section: Coding Gene and Protein Biomarkers In Osf Tissuesmentioning
confidence: 99%